FINANCIAL RATIOS PREDICTORS OF FINANCIAL SUSTAINABILITY OF THE BANKING SECTOR IN INDONESIA - Adiska Shabrina Sanfa; Ida Ida (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2023)
This study was conducted to predict the effect of financial ratios on the Financial Sustainability Ratio (FSR). The financial ratios used include Non-Performing Loan (NPL), Loan Deposit Ratio (LDR), Net Interest Margin (NIM), Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Operating Expenses to Operating Income (BOPO). Sampling using purposive sampling of as many as 36 Conventional Commercial Bank companies in Indonesia with a research period of 2019-2021 so that 108 observation data were obtained. The analysis method used is multiple linear regression analysis, and the test results show that NPL, LDR, NIM, CAR, and BOPO do not affect FSR. Meanwhile, ROA has a positive influence on FSR. The prediction results of this study estimate that NPL, LDR, NIM, ROA, CAR, and BOPO can influence 6.7% of FSR changes. Meanwhile, 93.3% is influenced by other variables not included in the research model. Therefore, the suggested implication for the company is the company needs to maintain bank performance to increase customer confidence in banks, and banks must have the ability to manage funds to increase ROA.Keywords: FSR, NPL, LDR, NIM,Â  ROA, CAR, BOPO